Desordenando el género de la genealogía: conflictos entre élites y desafíos a propósito de la dote (Barcelona, s. XVI-XVII) - Mariela Fargas Peñarrocha (Genre & Histoire)
Although the place of a wives’ dowries in any family system is constitutive of order in these families, their inalienability in Catalonia raises the question of how they were controlled and how they were transmitted by women. This study considers the strategies adopted, the decisions and the kinds of management they permitted, analysing the use of law and female practices to modify gender relations. By such means, they participated in the construction and deconstruction of genealogies and the formation of social trajectories. These female interventions can be seen with particular intensity at the moment when dowry inflation in seventeenth-century Barcelona helped to promote the multiplication of gender conflicts around the transmission of dowries.